2017
DOI: 10.5465/amp.2015.0111
|View full text |Cite
|
Sign up to set email alerts
|

Micro-entrepreneurs, Dependent Contractors, and Instaserfs: Understanding Online Labor Platform Workforces

Abstract: The rapidly growing number of people who find work via online labor platforms are not employees, nor do they necessarily fit traditional conceptualizations of independent contractors, freelancers, or the selfemployed. The ambiguous nature of their employment status and its implications for worker well-being have attracted substantial controversy, but to date most empirical research in this area has focused on the market efficiency of a single platform rather than on workers themselves and related human resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
324
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(337 citation statements)
references
References 51 publications
6
324
1
6
Order By: Relevance
“…In recent years, the societal and managerial implications of algorithms have spawned much public debate and drawn increasing attention from scholars [4,5,7]. With research into the impacts of algorithms on human workers and work practices still in its nascent stages, one area of study that remains underexplored is the impact of algorithmic management on gig-workers' perceptions of organizational support [4,8]. Perceived organizational support (POS) is the degree to which employees believe that their "organization values their contributions and cares about their well-being" [9, p. 698].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, the societal and managerial implications of algorithms have spawned much public debate and drawn increasing attention from scholars [4,5,7]. With research into the impacts of algorithms on human workers and work practices still in its nascent stages, one area of study that remains underexplored is the impact of algorithmic management on gig-workers' perceptions of organizational support [4,8]. Perceived organizational support (POS) is the degree to which employees believe that their "organization values their contributions and cares about their well-being" [9, p. 698].…”
Section: Introductionmentioning
confidence: 99%
“…While the notion of POS may, at first thought, seem irrelevant to the gig-work context given that independent work is typically defined in part by its lack of organizational support [8], and where workers are not employees and have no official human supervisor, POS has been found to apply in non-traditional work contexts akin to gig-work like contract work [12]. Such research has not only demonstrated that contingent workers can, and do, experience POS, but that they form perceptions of support from multiple organizational relationships, thereby suggesting the existence of unique antecedents for each relational source of POS [12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations